Paradigma al-Qur’an: Model Analisis Tafsir Maqasidi dalam Pemikiran Kuntowijoyo - Kusmana Kusmana (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2015)
This article assumes that Kuntowijoyo’s thought can be grouped into the maqasidi thought movement, because of his treatment of the objectivication of the verses of the Qur’an in search for God’s intention based on the scientific measurement. His difference from the thinkers of maqasidi in general lies on the use of epistemology. Maqasidi thinkers uses in general usul al-fiqh as their epistemological tool of analysis, whereas Kuntowijoyo deploys social sciences’ epistemology. This library research finds that the characteristics of Kuntowijoyo’s interpretation of the Qur’an can be included into the spirit of maqasidi scientific interpretation with a tendency of con- structing scientific knowledge based on the Qur’an. His characteristics of tafsir maqasidi can be grouped as manhaj din (religious methodology) atau in his word, (Quranic paradigm.)